Passion Fruit Peel in Growing Rabbits Feed (Revista Ciência Agronômica, 2021)
The use of alternative foods for rabbits aims to reduce production costs, due to their ability to extractingnutrients from non-conventional feeds. Thus, passion fruit peel (PFP) appears as a potential use in feeding rabbits.This study aimed to determine the chemical and energetic composition of PFP and evaluate the effects of inclusionfor growing rabbits. For the digestibility trial, 24 rabbits were distributed between two treatments (reference rationand test ration, composed of 70% reference ration and 30% PFP) with 12 replications of one animal per plot. For theperformance trial, 120 rabbits were distributed within a randomized block design, in a 5x2 factorial arrangement, with 5levels of inclusion of PFP (0, 8, 16, 24, 32%) and 2 sexes (male and female) corresponding to a total of 10 treatmentswith 12 replications each. PFP had 10.99% CP, 6.25% EE, 47.40% ADF, 54.66% NDF and 4,156.50 kcal DE/kg, on a drymatter. The inclusion of PFP did not influence the final weight and weight gain of rabbits, however it was observed thatrabbits fed at the level of 32% inclusion of PFP consumed less amount of feed, with no negative effect on performance.Decreased cholesterol and triglyceride levels were observed in relation to control and an increase of creatinine inrabbit’s blood. As there was an improvement in the economic parameters without affecting the performance and carcasscharacteristics, it’s recommended to include this ingredient up to level of 32% in the feed for growing rabbits.